THE IMPACT OF TRANSLATION TECHNIQUES TOWARD TRANSLATION QUALITY OF MICOAGGRESSION EXPRESSIONS TO LGBT IN BOYS DON’T CRY SUBTITLE - Kennia Wikanditha, M.R. Nababan; Riyadi Santosa (English Education Study Program STKIP PGRI Pacitan, 2022)
There are so many American films that use LGBT as the theme now in mainstream media such asNetflix, HBO, and Amazon Premium. Some of those films have been streamed in Indonesia.However, there might be some problems regarding the translated subtitle because Indonesiadoesn’t have as many gendered-languages as America. The aims of this research are to identifythe translation techniques and translation quality of microaggression expressions in Boys Don’tCry movie subtitle. This research uses descriptive qualitative method. This qualitative descriptiveresearch is an embedded-cased study and a product-oriented of translation research. The sourcedata of the research are microaggression expressions directed toward LGBT in Boys Don’t Cry.The data are collected through document analysist and FGD (Focus Group Discussion). Theresults of this research reveal that the translation techniques found in.